Reflective interpersonal therapy for children and parents : mind that child! : a new way of helping parents and children with extreme conduct disorder - 325034 Roff, Hermione (Chichester, England : John Wiley & Sons, 2008)
Includes bibliographical references (p. 293-295) and index.